Sequence architecture and depositional evolution of the northern continental slope of the South China Sea: responses to tectonic processes and changes in sea level. (7th April 2017) - Lin, Changsong; Jiang, Jing; Shi, Hesheng; Zhang, Zhongtao; Liu, Jingyan; Qin, Chenggang; Li, Hao; Ran, Huaijiang; Wei, An; Tian, Hongxun; Xing, Zuochang; Yao, Qingyu
Abstract: The continental slopes of the South China Sea (SCS), the largest marginal sea on the continental shelf of Southeast Asia, are among the most significant shelf‐margin basins in the world because of their abundant petroleum resources and a developmental history related to sea floor spreading since Late Oligocene time. Based on integrated analyses of seismic, well‐logging and core data, we systematically document the sequence architecture and depositional evolution of the northern continental slope of the SCS and reveal its responses to tectonism, sea‐level change and sediment supply. The infill of this shelf‐margin basin can be divided into seven composite sequences (CS1–CS7) that are bounded by regional unconformities. Composite sequences CS3 to CS7 have formed since Late Oligocene time, and each of them generally reflects a regional transgressive–regressive cycle. These large cycles can be further divided into 20 sequences that are defined by local unconformities or transgressive–regressive boundaries. Depositional–geomorphological systems represented on the continental slope mainly include shelf‐edge deltas, prodelta‐slope fans, clinoforms of the shelf‐margin slope, unidirectionally migrating slope channels, incised slope valleys, muddy slope fans, slope slump‐debris‐flow complexes and large‐scale soft‐sediment deformation of bedding. Changing sea levels, reflected by evidence from sequence architecture in the study area, are generally comparable with those of the Haq (1987) global sea level curve, whereas the regional transgressions and regressions were apparently controlled by tectonic uplift and subsidence. Composite sequences CS3 and CS4 formed from Late Oligocene to Middle Miocene time and represent continental‐slope deposition during a time of northwest‐northeast seafloor spreading and subsequent development of sub‐basins in the southwest‐central SCS. The development of composite sequences CS5 to CS7 after Middle Miocene time was obviously influenced by the Dongsha Movement during convergence between the SCS and Philippine Sea plates. Climatic variations and monsoon intensification may have enhanced sediment supply during Late Oligocene‒Early Miocene (25–21 Ma) and Late Pliocene‒Pleistocene (3–0.8 Ma) times. This study indicates that shelf‐edge delta and associated slope fan systems are the most important oil/gas‐bearing reservoirs in the SCS continental‐slope area.